Hatred has no future new thinking on relations with Japan - Ma, Licheng
The year was 2002 - the 20th anniversary of the normalization of Sino-Japanese relations, but also a time when relations grew sharply frostier over the prime minister's visit to Yasukuni Shrine. Into this fray dropped Ma Licheng's 'New Thinking on Relations with Japan,' triggering a storm of debate in both China and Japan. Even now, more than a decade after the essay's publication, the New Thinking continues to have a major influence on policy discussions. While Sino-Japanese relations hit new turbulence over the Diaoyu/Senkaku Islands in 2012, the author remains optimistic that the bilateral issues can be resolved rationally and peacefully. Referencing the durability of the postwar peace between France and Germany, he argues that - for their own and the international community's sake - China and Japan can and must find ways to overcome their antagonisms and live in peace as complementary neighbors.